The NF‐κB‐modulated miR‐19a‐3p enhances malignancy of human ovarian cancer cells through inhibition of IGFBP‐3 expression. Issue 12 (12th September 2019) - Bai, Ru; Cui, Zhenhua; Ma, Yongjing; Wu, Yang; Wang, Ningping; Huang, Ling; Yao, Qing; Sun, Jianmin
Abstract: Ovarian cancer is the most lethal gynecologic malignancy due to the lack of symptoms until advanced stages, and new diagnosis and treatment strategy is in urgent need. In this study, we found higher expression of miR‐19a‐3p in ovarian cancer tissues compared with that in the adjacent normal tissues. By chromatin immunoprecipitation (ChIP) and electrophoretic mobility shift assay (EMSA) analysis, we showed that nuclear factor‐kappaB (NF‐κB) binds to the promoter of miR‐19a‐3p, leading to reduced expression in ovarian cancer cells. Further study indicated that miR‐19a‐3p inhibits the expression of insulin‐like growth factor binding protein‐3 (IGFBP‐3), resulting in enhanced growth and migration of ovarian cancer cells in vitro and tumor growth in vivo. These results showed that miR‐19a‐3p enhances the oncogenesis of ovarian cancer through inhibition of IGFBP‐3 expression, and which can be inhibited by NF‐κB, suggesting an NF‐κB/miR‐19a‐3p/IGFBP‐3 pathway in the oncogenesis of ovarian cancer, which expands our understanding of ovarian cancer and they may contribute to the development of new diagnosis and treatment of ovarian cancer.